The role of the ω phase on the non-classical precipitation of the α phase in metastable β-titanium alloys. (15th January 2016) - Zheng, Yufeng; Williams, Robert E.A.; Sosa, John M.; Wang, Yunzhi; Banerjee, Rajarshi; Fraser, Hamish L.
Graphical abstract: Abstract: The metastable β-Ti alloy, Ti-5553, has been heat-treated to permit a determination of the role of the ω phase on non-classical precipitation of the α phase. Thus, samples containing the athermal ω phase have been up-quenched to 600°C. The observations made are consistent with the activation of the non-classical, pseudo-spinodal, nucleation mechanism, with the ω phase playing essentially no direct role. The α/β interfacial structures have been shown to exhibit significant degrees of coherency compared with those in conventional α/β alloys, and implications of this on lowering the interfacial energy, and so the activation for nucleation, are discussed.